Pentingnya Etika Publik, Akuntabilitas Publik Dalam Strategi Perencanaan Penggelolaan Kawasan Pelabuhan Penyebrangan - Prasetyo, Eko (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
In the management of crossing port areas, public ethics and accountability are crucial elements in strategic planning. This study aims to analyze the role of public ethics in creating transparency and public trust in resource management. Additionally, public accountability is expected to enhance community participation and support decisions oriented toward public welfare. Using a descriptive-qualitative approach, this research explores best practices in the implementation of ethics and accountability, as well as the challenges faced in the context of port area management. The findings indicate that the application of ethical and accountability principles not only improves management performance but also strengthens the legitimacy and responsiveness of the government in facing social dynamics. This study is expected to provide strategic recommendations for port area managers in formulating more inclusive and sustainable policies